International climate finance from a global perspective - Sherri Ombuya; Igor Shishlov; Axel Michaelowa (Austrian Foundation for Development Research (ÖFSE), 2023)
The Paris Agreement reaffirmed the commitment to provide USD 100 billion in international climate finance to developing countries by 2020. This Working Paper delves into the history and challenges of international climate finance. We emphasize the complexities tied to diverse definitions and accounting practices, leading to disputes over climate finance figures, as well as the struggle of developed countries to meet the USD 100 billion annual target. With the need to mobilize finance for addressing loss and damage (L&D) gaining traction in UN climate negotiations, we examine how similar challenges may hinder progress on the L&D agenda. Furthermore, we stress the importance of fostering trust between donor and recipient countries in the context of financial support pledges under the Paris Agreement. We identify how key negotiation processes, like the New Collective Quantified Goal on Climate Finance (NCGG), have the potential to change the status quo.
Keywords: 330; International Climate Finance; Loss and Damage; Climate Finance Accounting; Adaptation Finance; Conference of the Parties (COP)